Utility of CD200 expression and CD20 antibody binding capacity in differentiating chronic lymphocytic leukemia from other chronic lymphoproliferative disorders - R Poongodi; Neelam Varma; Shano Naseem; Bose Parveen; Subhash Varma (Wolters Kluwer Medknow Publications, 2018)
Background: Chronic lymphoproliferative disorders (CLPDs) are heterogeneous group of disorders with variable clinical presentations and outcomes. Therefore, accurate classification is crucial for treatment planning. At present, flow cytometry immunophenotyping (FCM-IPT) is a useful tool for diagnosing these diseases. However, overlapping immunophenotypes do exist. Recently, differential expression of CD200 and variation in number of CD20 antibody bound per cell (ABC) in different CLPDs has been reported. Materials and Methods: Seventy-seven CLPD cases were analyzed by FCM-IPT for CD200 expression, and Quantibrite bead was used to calculate CD20 ABC. Results: Variability in CD200 expression can help in the differentiation of chronic lymphocytic leukemia (CLL) and hairy cell leukemia (HCL) from other CLPDs. CD200 was brightly expressed in 100% CLL cases, having homogenous bright (2+) intensity. On the contrary, CD200 was uniformly negative in all Mantle cell lymphoma cases except 1, in which the intensity was dim, and the mean fluorescence intensity was significantly lower than CLL. Furthermore, all HCL cases showed bright expression of CD200, thereby making it useful in differentiation from other CLPD with villous lymphocytes. Evaluation of CD20 ABC showed that it differs among various CLPD and was significantly lowest in CLL and highest in HCL both on peripheral blood and bone marrow samples. Conclusion: Our results support the fact that CD200 can be added to routine CLPD panel as it is useful in subcategorizing them. However, inclusion of CD20 ABC to routine panel does not seem plausible but may be done for difficult diagnostic cases or where anti-CD20 therapy is planned.